(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
In this study, we investigated the effects of methanolic extract of Tamarindus indica (TI) seeds on anti-inflammatory and analgesic activities in vivo using rat as an animal model at the doses of 100 mg/kg, 200 mg/kg and 400 mg/kg body weight. The anti-inflammatory activities were investigated by utilizing carrageenan induced paw edema in rat. The analgesic activity was examined against tail immersion method in rats. The results showed that TI significantly (p<0.01) reduced carrageenan induced paw edema in rats. In tail immersion method, methanolic extract of Tamarindus indica has shown significant (p<0.01) increase in reaction time of tail in water maintained at 55°C indicating analgesic activity. Preliminary phytochemical screening of the extract revealed the presence of alkaloids, tannins, saponins, glycosides and flavonoids. These results demonstrated that the methanolic extract of Tamarindus indica (TI) seed exhibited significant analgesic and anti-inflammatory activities.